Tingkat kesukaan cookies mocaf dengan penambahan koro benguk (Mucuna pruriens) dan labu kuning (Cucurbita moschata) pada variasi suhu pengeringan - Rini Nuraini Rohmatningsih; Agus Slamet; Bayu Kanetro (AGROINTEK, 2025)
Consumer preference for gluten-free products is increasing, which aligns with health awareness. Mocaf cookies with mucuna pruriens and pumpkin can be a new alternative for healthy snack innovation. This research aims to design and determine the optimal formulation of mocaf mucuna pruriens pumpkin cookies based on parameters affecting the process and favored by panelists. A Completely Randomized Design (CRD) Factorial method with two replications was applied, consisting of two factors. The first factor is the proportion of mucuna pruriens and pumpkin addition, which consists of six variations: 10:60 (F1), 20:50 (F2), 30:40 (F3), 40:30 (F4), 50:20 (F5), and 10:60 (F6). The second factor is the difference in drying temperature, namely 110 ℃ (T1) and 120 ℃ (T2). This method was conducted to evaluate the effect of adding mucuna pruriens and pumpkin on the qualitative characteristics of cookies, such as organoleptic tests. Sensory properties testing was performed using a hedonic test that included evaluations of taste, aroma, color, texture, aftertaste, and overall product. The preference test was applied to 27 trained panelists with a rating scale of 1 (strongly dislike) to 7 (strongly like) conducted in 2 replications. The data obtained were analyzed using Analysis of Variance (ANOVA) to determine the effect of treatments and further analyzed using the Duncan Multiple Range Test (DMRT) at a 5 % significance level. Mocaf cookies with the addition of 40 % mucuna pruriens and 30 % pumpkin at a drying temperature of 120 ℃ were selected as the best mocaf cookies formulation according to the panelists.